Composite current collector, secondary battery and electronic device

By using composite fluid collection in lithium-ion batteries, the structure of the base film and conductive layer is regulated, and the bidirectional transmission of lithium ions is achieved, which solves the problem of lithium ion unidirectional transmission limiting the battery's rate performance and improves the battery's rate performance.

CN119481081APending Publication Date: 2025-02-18NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411718216.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Lithium ions can only be transmitted in one-way, limiting the battery's rate performance.

Method used

A composite liquid collecting fluid is adopted, which includes a base film and a conductive layer disposed on at least one surface of the base film, and bidirectional transmission of lithium ions is achieved by regulating the porosity, pore size and thickness of the base film and the conductive layer.

Benefits of technology

By transmitting lithium ions in both directions, the transmission path of lithium ions is shortened and the rate performance of the secondary battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481081A_ABST
    Figure CN119481081A_ABST
Patent Text Reader

Abstract

The invention provides a composite current collector, a secondary battery and an electronic device, the composite current collector comprises a base film and a conductive layer arranged on at least one surface of the base film, the base film comprises at least one of a polypropylene film, a polyethylene film, a polyimide film or aramid fiber, the porosity of the base film is P1%, 30 < = P1 < = 80, the aperture of the base film is phi1nm, 200 < = phi1 < = 1000, and the thickness of the conductive layer is 0.1-0.5 mm. The porosity of the conductive layer is P2%, 10 < = P2 < = 75, the aperture of the conductive layer is phi 2nm, and 100 < = phi 2 < = 800. The composite current collector comprises the structure, the type, the porosity and the aperture of the base membrane and the porosity and the aperture of the conductive layer are within the range of the application, so that lithium ions can be bidirectionally transmitted, the transmission path of the lithium ions is shortened, and the rate capability of the secondary battery is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a composite current collector, a secondary battery and an electronic device. Background Art

[0002] Lithium-ion batteries are usually composed of positive electrode sheets, negative electrode sheets, separators, and electrolytes. The positive electrode sheets are mostly made of positive electrode material layers coated on positive electrode current collector aluminum foil, and the negative electrode sheets are mostly made of negative electrode material layers coated on negative electrode current collector copper foil. Copper foil and aluminum foil are non-porous sheets that cannot penetrate electrolytes. Lithium ions cannot be transmitted through copper foil or aluminum foil. Lithium ions can only be transmitted in one direction, which will limit the transmission of lithium ions.

[0003] Therefore, there is an urgent need to provide a composite current collector that can enable bidirectional transmission of lithium ions, shorten the transmission path of lithium ions, and help improve the rate performance of lithium ion batteries. Summary of the invention

[0004] The purpose of the present application is to provide a composite current collector, a secondary battery and an electronic device, which can enable bidirectional transmission of lithium ions, shorten the transmission path of lithium ions, and help improve the rate performance of the secondary battery.

[0005] The first aspect of the present application provides a composite current collector, which includes a base film and a conductive layer arranged on at least one surface of the base film, the base film includes at least one of a polypropylene film, a polyethylene film, a polyimide film or an aramid film, the porosity of the base film is P1%, 30≤P1≤80, the pore size of the base film is Φ1nm, 200≤Φ1≤1000, the porosity of the conductive layer is P2%, 10≤P2≤75, and the pore size of the conductive layer is Φ2nm, 100≤Φ2≤800. The composite current collector includes the above structure, and by adjusting P1, P2, Φ1, and Φ2 within the scope of the present application, the rate performance of the secondary battery can be improved.

[0006] In some embodiments of the present application, 500≤Φ1≤800, and / or 300≤Φ2≤600. By adjusting Φ1 and Φ2 within the scope of the present application, the rate performance of the secondary battery can be improved.

[0007] In some embodiments of the present application, 1≤P1 / P2≤2, and / or 1≤Φ1 / Φ2≤2. By adjusting P1 / P2 and Φ1 / Φ2 within the scope of the present application, the rate performance of the secondary battery is further improved.

[0008] In some embodiments of the present application, the thickness of the base film is d1 μm, 2≤d1≤10. By adjusting the thickness d1 of the base film within the scope of the present application, the rate performance of the secondary battery is further improved, and the energy density of the secondary battery is also improved.

[0009] In some embodiments of the present application, the thickness of the conductive layer is d2 μm, 0.1≤d2≤5. By adjusting the thickness d2 of the conductive layer within the range of the present application, the rate performance of the secondary battery is further improved, and the secondary battery has a higher energy density.

[0010] In some embodiments of the present application, 5≤d1 / d2≤10. By adjusting d1 / d2 within the scope of the present application, the secondary battery has good rate performance and high energy density.

[0011] In some embodiments of the present application, the surface resistance of the conductive layer is R mΩ / sq, 10≤R≤50. By adjusting the surface resistance of the conductive layer within the scope of the present application, the rate performance of the secondary battery is further improved.

[0012] In some embodiments of the present application, the composite current collector includes a base film and a conductive layer disposed on one surface of the base film, the conductive layer includes any one of a metal layer or a conductive carbon layer; the material of the metal layer includes any one of copper, aluminum, zinc, titanium, nickel or silver; the conductive carbon layer includes conductive carbon and a binder, the conductive carbon includes at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the binder includes at least one of polyvinylidene fluoride, styrene butadiene rubber or acrylate; based on the mass of the conductive carbon layer, the mass percentage of the conductive carbon is W1%, 50≤W1≤95. The composite current collector includes the above structure, which is conducive to improving the rate performance of the secondary battery.

[0013] In some embodiments of the present application, the composite current collector includes a base film, a first conductive layer and a second conductive layer, the base film is disposed between the first conductive layer and the second conductive layer, the first conductive layer includes a first metal layer, the second conductive layer includes a second metal layer, the material of the first metal layer includes at least one of aluminum, nickel or silver, and the material of the second metal layer includes at least one of copper, nickel or silver. The composite current collector includes the above structure, further improving the rate performance of the secondary battery.

[0014] In some embodiments of the present application, the composite current collector includes a base film, a first conductive layer and a second conductive layer, the base film is arranged between the first conductive layer and the second conductive layer; the first conductive layer includes a first conductive carbon layer, the second conductive layer includes a second conductive carbon layer, the first conductive carbon layer includes a first conductive carbon and a first binder, the second conductive carbon layer includes a second conductive carbon and a second binder, the first conductive carbon and the second conductive carbon are each independently selected from at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the first binder and the second binder are each independently selected from at least one of polyvinylidene fluoride, styrene-butadiene rubber or acrylate. Based on the mass of the first conductive carbon layer, the mass percentage of the first conductive carbon is W2%, based on the mass of the second conductive carbon layer, the mass percentage of the second conductive carbon is W3%, 1<W2 / W3≤2. The composite current collector includes the above structure, which further improves the rate performance of the secondary battery.

[0015] In some embodiments of the present application, the bonding force between the base film and the conductive layer is 2 N / m to 200 N / m. By adjusting the bonding force between the base film and the conductive layer within the scope of the present application, the rate performance of the secondary battery is further improved.

[0016] The second aspect of the present application provides a secondary battery, which includes the composite current collector described in the first aspect of the present application. The secondary battery of the present application meets the above characteristics and can enable the secondary battery to have good rate performance.

[0017] The third aspect of the present application provides an electronic device, which includes the secondary battery described in the second aspect of the present application. Therefore, the electronic device provided by the present application has good rate performance.

[0018] Beneficial effects of this application:

[0019] The present application provides a composite current collector, a secondary battery and an electronic device, wherein the composite current collector comprises a base film and a conductive layer disposed on at least one surface of the base film, wherein the base film comprises at least one of a polypropylene film, a polyethylene film, a polyimide film or an aramid film, wherein the porosity of the base film is P1%, 30≤P1≤80, the pore size of the base film is Φ1nm, 200≤Φ1≤1000, the porosity of the conductive layer is P2%, 10≤P2≤75, and the pore size of the conductive layer is Φ2nm, 100≤Φ2≤800. The composite current collector comprises the above structure, and the type, porosity and pore size of the base film and the porosity and pore size of the conductive layer are within the scope of the present application, which can enable bidirectional transmission of lithium ions, shorten the transmission path of lithium ions, and is conducive to improving the rate performance of the secondary battery.

[0020] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0022] Figure 1 A schematic diagram of the structure of a lithium-ion battery prepared by a lamination process using the composite current collector prepared in Example 1-1 of the present application;

[0023] Figure 2 A schematic diagram of the structure of a lithium-ion battery prepared by a lamination process using the composite current collector prepared in Example 3-1 of the present application;

[0024] Figure 3 A schematic diagram of the structure of a lithium-ion battery prepared by a lamination process using the composite current collector prepared in Examples 3-8 of the present application;

[0025] Figure 4 A schematic diagram of the surface square resistance test method of the present application;

[0026] Figure 5 This is a surface scanning electron microscope image of the base film of the composite current collector prepared in Example 1-1 of the present application;

[0027] Figure 6 This is a surface scanning electron microscope image of the conductive layer (copper) of the composite current collector prepared in Example 1-1 of the present application;

[0028] Figure 7 This is a surface scanning electron microscope image of the conductive layer (aluminum) of the composite current collector prepared in Example 1-1 of the present application. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0030] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0031] The first aspect of the present application provides a composite current collector, which includes a base film and a conductive layer arranged on at least one surface of the base film, the base film includes at least one of a polypropylene (PP) film, a polyethylene (PE) film, a polyimide (PI) film or an aramid film, the porosity of the base film is P1%, 30≤P1≤80, the pore size of the base film is Φ1nm, 200≤Φ1≤1000, the porosity of the conductive layer is P2%, 10≤P2≤75, the pore size of the conductive layer is Φ2nm, 100≤Φ2≤800, preferably, 500≤Φ1≤800, and / or 300≤Φ2≤600. For example, P1 can be 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, or a range consisting of any two of them; Φ1 can be 200, 300, 400, 500, 600, 700, 800, 900, 1000, or a range consisting of any two of them; P2 can be 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or a range consisting of any two of them; Φ2 can be 100, 200, 300, 400, 500, 600, 700, 800, or a range consisting of any two of them.

[0032] The inventors have found that the composite current collector includes a base membrane and a conductive layer arranged on at least one surface of the base membrane. The type of the base membrane is within the scope of this application and the conductive layer is a porous structure. A positive electrode material layer and / or a negative electrode material layer are arranged on the surface of the conductive layer. Lithium ions can be transmitted through the base membrane. At the same time, lithium ions can also be transmitted through the positive electrode material layer and / or the negative electrode material layer, so that lithium ions can be transmitted bidirectionally, shortening the transmission path of lithium ions, which is beneficial to improving the rate performance of the secondary battery. Since the conductive layer will block part of the pores of the base membrane, the base membrane needs a larger porosity to effectively ensure the porosity of the composite current collector; in addition, if the pore size of the base membrane is too large, the conductive layer will short-circuit, and if the pore size of the base membrane is too small, the conductive layer will be dense; at the same time, the pore size of the conductive layer needs to be smaller than the pore size of the base membrane. Therefore, P1, P2, Φ1, and Φ2 are regulated within the scope of this application, the porosity of the base membrane matches the porosity of the conductive layer, and the pore size of the base membrane matches the pore size of the conductive layer, which is beneficial to the bidirectional transmission of lithium ions, shortens the transmission path of lithium ions, and thus improves the rate performance of the secondary battery.

[0033] In some embodiments of the present application, P1≥P2, Φ1≥Φ2. In some embodiments of the present application, P1>P2, Φ1>Φ2. The size relationship between P1 and P2, and the size relationship between Φ1 and Φ2 are within the scope of the present application, and can better meet the production process requirements.

[0034] In some embodiments of the present application, 1≤P1 / P2≤2, and / or 1≤Φ1 / Φ2≤2. For example, P1 / P2 can be 1, 1.2, 1.4, 1.6, 1.8, 2, or a range consisting of any two of these values; Φ1 / Φ2 can be 1, 1.2, 1.4, 1.6, 1.8, 2, or a range consisting of any two of these values. By regulating P1 / P2 and Φ1 / Φ2 within the scope of the present application, the porosity of the base film and the porosity of the conductive layer match each other, and the pore size of the base film and the pore size of the conductive layer match each other, which helps to further realize the bidirectional transmission of lithium ions, further shorten the transmission path of lithium ions, and thus further improve the rate performance of the secondary battery.

[0035] In some embodiments of the present application, the thickness of the base film is d1 μm, 2≤d1≤10. For example, d1 can be 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range consisting of any two of these values. The thickness of the composite current collector affects the energy density and ion transmission path of the secondary battery. By regulating the thickness d1 of the base film within the scope of the present application, the base film has a suitable thickness, which helps to shorten the ion transmission path, thereby further improving the rate performance of the secondary battery and improving the energy density of the secondary battery.

[0036] In some embodiments of the present application, the thickness of the conductive layer is d2 μm, 0.1≤d2≤5. For example, d2 can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of these values. The thickness of the conductive layer affects the conductivity of the conductive layer; as the thickness of the conductive layer increases, the conductivity of the conductive layer increases, but the energy density decreases. By regulating the thickness d2 of the conductive layer within the scope of the present application, the conductive layer has a suitable thickness, the conductive layer has a higher conductivity, which is conducive to electron transmission, thereby further improving the rate performance of the secondary battery, and the secondary battery has a higher energy density.

[0037] In some embodiments of the present application, 5≤d1 / d2≤10. For example, d1 / d2 can be 5, 6, 7, 8, 9, 10 or a range consisting of any two of these values. By regulating d1 / d2 within the scope of the present application, the thickness of the base film and the conductive layer of the composite current collector are reasonably regulated, which helps to shorten the lithium ion transmission path, and the conductive layer has a high conductivity, which is conducive to the transmission of lithium ions and electrons. The secondary battery has good rate performance and a high energy density.

[0038] In some embodiments of the present application, the Young's modulus of the composite current collector is E GPa, 0.05≤E≤25. For example, E can be 0.05, 1, 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, or a range consisting of any two of these values. The composite current collector needs to undergo a cold pressing process. By regulating the Young's modulus of the composite current collector within the scope of the present application, the composite current collector can have a higher strength, thereby further reducing the risk of pole piece breakage during the production process of the secondary battery.

[0039] In some embodiments of the present application, the surface square resistance of the conductive layer is R mΩ / sq, 10≤R≤50. For example, R can be 10, 15, 20, 25, 30, 35, 40, 45, 50, or a range consisting of any two of these values. The surface square resistance of the composite current collector conductive layer is within the scope of the present application, which is conducive to improving the electronic impedance and further improving the rate performance of the secondary battery.

[0040] In some embodiments of the present application, the composite current collector includes a base film and a conductive layer disposed on one surface of the base film, the conductive layer includes any one of a metal layer or a conductive carbon layer; the material of the metal layer includes any one of copper, aluminum, zinc, titanium, nickel or silver; the conductive carbon layer includes conductive carbon and a binder, the conductive carbon includes at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber or acrylate; based on the mass of the conductive carbon layer, the mass percentage of the conductive carbon is W1%, 50≤W1≤95. For example, the mass percentage of the conductive carbon can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or a range consisting of any two of the values. Based on the mass of the conductive carbon layer, the mass percentage of the binder is 5% to 50%. For example, the mass percentage of the binder can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of the values. The conductive layer of the composite current collector includes any one of a metal layer or a conductive carbon layer. When the conductive layer includes a metal layer and is selected from the above materials as the material of the metal layer, or when the conductive layer includes a conductive carbon layer and the mass percentage of the conductive carbon is regulated within the scope of the present application, it is beneficial to electron transmission, and lithium ions can be bidirectionally transmitted, shortening the transmission path of lithium ions, which is beneficial to improving the rate performance of the secondary battery.

[0041] In some embodiments of the present application, the composite current collector includes a base film, a first conductive layer and a second conductive layer, the base film is arranged between the first conductive layer and the second conductive layer, the first conductive layer includes a first metal layer, the second conductive layer includes a second metal layer, the material of the first metal layer includes at least one of aluminum, nickel or silver, and the material of the second metal layer includes at least one of copper, nickel or silver. The composite current collector includes the above structure, and the materials used for the first metal layer and the second metal layer are within the scope of the present application, which is conducive to electron transmission, and at the same time enables bidirectional transmission of lithium ions, shortens the transmission path of lithium ions, and further improves the rate performance of the secondary battery.

[0042] In some embodiments of the present application, the composite current collector includes a base film, a first conductive layer and a second conductive layer. A positive electrode material layer is arranged on the surface of the first conductive layer of the composite current collector away from the base film, and a negative electrode material layer is arranged on the surface of the second conductive layer of the composite current collector away from the base film. At this time, the resistance between the first conductive layer and the second conductive layer is infinite.

[0043] In some embodiments of the present application, the composite current collector includes a base film, a first conductive layer and a second conductive layer, the base film is arranged between the first conductive layer and the second conductive layer, the first conductive layer includes a first metal layer, the material of the first metal layer includes at least one of aluminum, nickel or silver, the porosity of the first metal layer is P21%, 10≤P21≤75, the pore size is Φ21nm, 300≤Φ21≤600, and the thickness is d21μm, 0.1≤d21≤5; the second conductive layer includes a second metal layer, the material of the second metal layer includes at least one of copper, nickel or silver, the porosity of the second metal layer is P22%, 10≤P22≤75, the pore size is Φ22nm, 300≤Φ22≤600, the thickness is d22μm, 0.1≤d22≤5. 0.5≤P21 / P22≤1.5, 0.5≤Φ21 / Φ22≤1.5, 0.5≤d21 / d22≤3. By regulating the pore size, porosity and thickness of the first metal layer and the second metal layer within the scope of this application, and regulating the values ​​of P21 / P22, Φ21 / Φ22, and d21 / d22 within the scope of this application, the requirements of electron transmission and ion transmission between the positive electrode plate and the negative electrode plate can be met, and the rate performance of the secondary battery can be further improved.

[0044] In some embodiments of the present application, the composite current collector includes a base film, a first conductive layer and a second conductive layer, the base film is arranged between the first conductive layer and the second conductive layer, a positive electrode material layer is arranged on the surface of the first conductive layer of the composite current collector away from the base film, and a negative electrode material layer is arranged on the surface of the second conductive layer of the composite current collector away from the base film. The first conductive layer includes a first conductive carbon layer, the second conductive layer includes a second conductive carbon layer, the first conductive carbon layer includes a first conductive carbon and a first binder, and the second conductive carbon layer includes a second conductive carbon and a second binder. The first conductive carbon and the second conductive carbon are each independently selected from at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the first binder and the second binder are each independently selected from at least one of polyvinylidene fluoride, styrene-butadiene rubber or acrylate. Based on the mass of the first conductive carbon layer, the mass percentage of the first conductive carbon is W2%, based on the mass of the second conductive carbon layer, the mass percentage of the second conductive carbon is W3%, 1<W2 / W3≤2. For example, W2 / W3 can be 1.01, 1.1, 1.2, 1.4, 1.6, 1.8, 2 or a range consisting of any two of these values. A negative electrode material layer is disposed on the surface of the second conductive layer away from the base film, and the electronic conductivity of the negative electrode material layer is relatively strong. A positive electrode material layer is disposed on the surface of the first conductive layer away from the base film, and the electronic conductivity of the positive electrode material layer is relatively weak. Therefore, it is necessary to increase the mass percentage of the conductive carbon in the first conductive layer, and adjust W2 / W3 within the scope of this application, which can improve the electronic conductivity of the composite current collector, thereby further improving the rate performance of the secondary battery.

[0045] In some embodiments of the present application, 50≤W2≤95, 50≤W3≤95. Based on the mass of the first conductive carbon layer, the mass percentage of the first binder is 5% to 50%, and based on the mass of the second conductive carbon layer, the mass percentage of the second binder is 5% to 50%. For example, W2 can be 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or a range consisting of any two of the values ​​therein; the mass percentage of the first binder can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of the values ​​therein; W3 can be 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or a range consisting of any two of the values ​​therein; the mass percentage of the second binder can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two of the values ​​therein.

[0046] In some embodiments of the present application, the composite current collector includes a base film, a first conductive layer and a second conductive layer, the base film is arranged between the first conductive layer and the second conductive layer, the first conductive layer includes a first conductive carbon layer, the first conductive carbon layer includes a first conductive carbon and a first binder, the porosity of the first conductive carbon layer is P23%, 10≤P23≤75, the pore size is Φ23nm, 300≤Φ23≤600, and the thickness is d23μm, 0.1≤d23≤5; the second conductive layer includes a second conductive carbon layer, the second conductive carbon layer includes a second conductive carbon and a second binder, the porosity of the second conductive carbon layer is P24%, 10≤P24≤75, the pore size is Φ24nm, 300≤Φ24≤600, the thickness is d24μm, 0.1≤d24≤5; 0.5≤P23 / P24≤1.5, 0.5≤Φ23 / Φ24≤1.5, 0.5≤d23 / d24≤3. By regulating the pore size, porosity and thickness of the first conductive carbon layer and the second conductive carbon layer within the scope of this application, and regulating the values ​​of P23 / P24, Φ23 / Φ24, and d23 / d24 within the scope of this application, the electron transmission and ion transmission requirements of the positive electrode and the negative electrode can be met, and the rate performance of the lithium-ion battery can be further improved.

[0047] In some embodiments of the present application, the bonding force between the base film and the conductive layer is 2N / m to 200N / m. For example, the bonding force between the base film and the conductive layer can be 2N / m, 10N / m, 20N / m, 30N / m, 40N / m, 50N / m, 60N / m, 70N / m, 80N / m, 90N / m, 100N / m, 110N / m, 120N / m, 130N / m, 140N / m, 150N / m, 170N / m, 180N / m, 190N / m, 200N / m or a range composed of any two values. By regulating the bonding force between the base film and the conductive layer within the scope of the present application, it is helpful for the base film and the conductive layer of the composite current collector to be firmly bonded, which helps the bidirectional transmission of lithium ions and shortens the transmission path of lithium ions, thereby further improving the rate performance of the secondary battery.

[0048] The present application has no particular restrictions on the preparation method of the composite current collector, and a preparation method known in the art can be used. For example, the preparation method of the composite current collector may include the following steps: using a sputtering method, setting the sputtering instrument time to 0.5 min to 20 min, and the sputtering rate to to The sputtering temperature is 85°C to 120°C, and a metal layer is sputtered on one surface of the base film to obtain a composite current collector. For example, the base film is placed on a sample stage of a thermal evaporator and evacuated to a vacuum degree of ≤10 -6 Torr, set the sputtering instrument time to 0.5min to 20min, and the sputtering rate to to The sputtering temperature is 85°C to 120°C, and the electron gun starts the electron beam to bombard the metal target until it evaporates and vaporizes. The gaseous particles of the metal are quickly transported to the surface of the base film on the sample stage under vacuum, and nucleate and grow on a surface of the base film. The metal target includes any one of copper, aluminum, zinc, titanium, nickel or silver. For example, the preparation method of the composite current collector may include the following steps: coating a conductive carbon layer on a surface of the base film by scraping to obtain a composite current collector.

[0049] For example, the preparation method of the composite current collector may include the following steps: using a sputtering method, setting the time of the sputtering instrument to 0.5 min to 20 min, and the sputtering rate to to The sputtering temperature is 85° C. to 120° C., and a metal layer is sputtered on both surfaces of the base film to obtain a composite current collector. For example, the preparation method of the composite current collector may include the following steps: coating a conductive carbon layer on both surfaces of the base film by blade coating to obtain a composite current collector.

[0050] The present application has no particular restrictions on the method of regulating the porosity P1 and pore size Φ1 of the base film, as long as the purpose of the present application can be achieved. For example, the porosity P1 and pore size Φ1 of the base film can be regulated by regulating the heat treatment temperature and / or tensile strength.

[0051] The present application has no particular limitation on the method for adjusting the thickness d1 of the base film, as long as the purpose of the present application can be achieved. For example, the thickness d1 of the base film can be adjusted by adjusting the casting thickness and / or stretching.

[0052] In this application, base membranes with different pore sizes, porosities, and thicknesses can be purchased, and the pore size, porosity, and thickness of the base membrane can be obtained by measurement, and the base membrane with the required pore size, porosity, and thickness can be selected. Among them, the specific test method of the pore size of the base membrane can refer to the relevant content of the base membrane pore size test in the "Composite current collector base membrane and conductive layer pore size test" in the "Testing methods and equipment" section; the specific test method of the porosity of the base membrane can refer to the relevant content of the base membrane porosity test in the "Composite current collector base membrane and conductive layer porosity test" in the "Testing methods and equipment" section; the specific test method of the thickness of the base membrane can refer to the relevant content of the base membrane thickness test in the "Thickness test" in the "Testing methods and equipment" section.

[0053] The present application has no particular restrictions on the method of regulating the porosity P2 and pore size Φ2 of the conductive layer, as long as the purpose of the present application can be achieved. For example, the porosity P2 and pore size Φ2 of the conductive layer can be regulated by regulating the sputtering rate of the conductive layer.

[0054] The present application has no particular limitation on the method for adjusting the thickness d2 of the conductive layer, as long as the purpose of the present application can be achieved. For example, the thickness d2 of the conductive layer can be adjusted by adjusting the sputtering weight per unit area of ​​the conductive layer.

[0055] The present application has no particular limitation on the method for adjusting the value of P1 / P2, as long as the purpose of the present application can be achieved. For example, the value of P1 / P2 can be adjusted by adjusting the values ​​of P1 and P2, and the method for adjusting P1 and P2 is as described above.

[0056] The present application has no particular limitation on the method for adjusting the value of Φ1 / Φ2, as long as the purpose of the present application can be achieved. For example, the value of Φ1 / Φ2 can be adjusted by adjusting the values ​​of Φ1 and Φ2, and the method for adjusting Φ1 and Φ2 is as described above.

[0057] The present application has no particular limitation on the method for adjusting the value of d1 / d2, as long as the purpose of the present application can be achieved. For example, the value of d1 / d2 can be adjusted by adjusting the values ​​of d1 and d2, and the method for adjusting d1 and d2 is as described above.

[0058] The present application has no particular restrictions on the manner of regulating the porosity P21 and pore size Φ21 of the first metal layer and the porosity P22 and pore size Φ22 of the second metal layer, as long as the purpose of the present application can be achieved. For example, the porosity P21 and pore size Φ21 of the first metal layer can be regulated by regulating the sputtering rate of the first metal layer; the porosity P22 and pore size Φ22 of the second metal layer can be regulated by regulating the sputtering rate of the second metal layer.

[0059] The present application has no particular restrictions on the method of adjusting the thickness d21 of the first metal layer and the thickness d22 of the second metal layer, as long as the purpose of the present application can be achieved. For example, the thickness d21 of the first metal layer can be adjusted by adjusting the sputtering weight per unit area of ​​the first metal layer; the thickness d22 of the second metal layer can be adjusted by adjusting the sputtering weight per unit area of ​​the second metal layer.

[0060] The present application has no particular restrictions on the method for adjusting the values ​​of P21 / P22, Φ21 / Φ22, and d21 / d22, as long as the purpose of the present application can be achieved. For example, the value of P21 / P22 can be adjusted by adjusting the values ​​of P21 and P22, and the methods for adjusting P21 and P22 are as described above; the value of Φ21 / Φ22 can be adjusted by adjusting the values ​​of Φ21 and Φ22, and the methods for adjusting Φ21 and Φ22 are as described above; the value of d21 / d22 can be adjusted by adjusting the values ​​of d21 and d22, and the methods for adjusting d21 and d22 are as described above.

[0061] The present application has no particular restrictions on the manner of regulating the porosity P23 and pore size Φ23 of the first conductive carbon layer and the porosity P24 and pore size Φ24 of the second conductive carbon layer, as long as the purpose of the present application can be achieved. For example, the porosity P23 and pore size Φ23 of the first conductive carbon layer can be regulated by regulating the solid content of the first conductive carbon layer slurry, the parameters of the coating machine nozzle, and the drying rate; the porosity P24 and pore size Φ24 of the second conductive carbon layer can be regulated by regulating the solid content of the second conductive carbon layer slurry, the parameters of the coating machine nozzle, and the drying rate.

[0062] The present application has no particular restrictions on the method of adjusting the thickness d23 of the first conductive carbon layer and the thickness d24 of the second conductive carbon layer, as long as the purpose of the present application can be achieved. For example, the thickness d23 of the first conductive carbon layer can be adjusted by adjusting the coating weight per unit area of ​​the first conductive carbon layer; the thickness d24 of the second conductive carbon layer can be adjusted by adjusting the coating weight per unit area of ​​the second conductive carbon layer.

[0063] The present application has no particular restrictions on the method for regulating the values ​​of P23 / P24, Φ23 / Φ24, and d23 / d24, as long as the purpose of the present application can be achieved. For example, the value of P23 / P24 can be regulated by regulating the respective values ​​of P23 and P24, and the methods for regulating P23 and P24 are as described above; the value of Φ23 / Φ24 can be regulated by regulating the respective values ​​of Φ23 and Φ24, and the methods for regulating Φ23 and Φ24 are as described above; the value of d23 / d24 can be regulated by regulating the respective values ​​of d23 and d24, and the methods for regulating d23 and d24 are as described above.

[0064] The present application has no particular restrictions on the manner of regulating the surface square resistance R of the conductive layer, as long as the purpose of the present application can be achieved. For example, the surface square resistance R of the conductive layer can be regulated by regulating the thickness of the conductive layer. When other conditions remain unchanged, the thickness of the conductive layer increases, and the surface square resistance R of the conductive layer decreases; the thickness of the conductive layer decreases, and the surface square resistance R of the conductive layer increases.

[0065] The present application has no particular restrictions on the method of regulating the Young's modulus E of the composite current collector, as long as the purpose of the present application can be achieved. For example, when the conductive layer includes a conductive carbon layer, the Young's modulus E of the composite current collector can be regulated by regulating the mass percentage of the binder in the conductive carbon layer; when the conductive layer includes a metal layer, the Young's modulus E of the composite current collector can be regulated by regulating the thickness, porosity, and pore size of the metal layer.

[0066] The present application has no particular restrictions on the method of regulating the mass percentage content W1 of the conductive carbon, as long as the purpose of the present application can be achieved. For example, the mass percentage content W1 of the conductive carbon can be regulated by regulating the mass of the added conductive carbon.

[0067] The present application has no particular restrictions on the method of adjusting the mass percentage content W2 of the first conductive carbon and the mass percentage content W3 of the second conductive carbon, as long as the purpose of the present application can be achieved. For example, the mass percentage content W2 of the first conductive carbon can be adjusted by adjusting the mass of the added first conductive carbon; the mass percentage content W3 of the second conductive carbon can be adjusted by adjusting the mass of the added second conductive carbon.

[0068] The present application has no particular limitation on the method of adjusting W2 / W3, as long as the purpose of the present application can be achieved. For example, the value of W2 / W3 can be adjusted by adjusting the values ​​of W2 and W3, and the method of adjusting W2 and W3 is as described above.

[0069] The present application does not particularly limit the method of regulating the bonding force between the base film and the conductive layer, as long as the purpose of the present application can be achieved. For example, when the conductive layer is a conductive carbon layer, the bonding force between the base film and the conductive layer can be regulated by regulating the mass percentage of the binder in the conductive layer. Increasing the mass percentage of the binder in the conductive layer increases the bonding force between the base film and the conductive layer; reducing the mass percentage of the binder in the conductive layer reduces the bonding force between the base film and the conductive layer. For example, when the conductive layer is a metal layer, the bonding force between the base film and the conductive layer can be regulated by regulating the sputtering rate and / or sputtering temperature of the metal layer. In the present application, the change in the bonding force between the base film and the conductive layer has a relatively small effect on the rate performance of the secondary battery, and will affect the cycle performance of the secondary battery.

[0070] The second aspect of the present application provides a secondary battery, which includes the composite current collector described in the first aspect of the present application.

[0071] In some embodiments of the present application, the negative electrode plate includes a composite current collector and a negative electrode material layer located on one surface of the composite current collector, the composite current collector includes a base film and a conductive layer disposed on one surface of the base film, and the conductive layer disposed on the surface with the negative electrode material layer is the second conductive layer. The positive electrode plate includes a composite current collector and a positive electrode material layer located on one surface of the composite current collector, the composite current collector includes a base film and a conductive layer disposed on one surface of the base film, and the conductive layer disposed on the surface with the positive electrode material layer is the first conductive layer. Specifically, as Figure 1As shown, the negative electrode sheet 1 includes a composite current collector 10 and a negative electrode material layer 11 located on one surface of the composite current collector 10, and the composite current collector 10 includes a base film 101 and a second conductive layer 102 disposed on one surface of the base film 101; the positive electrode sheet 2 includes a composite current collector 10 and a positive electrode material layer 21 located on one surface of the composite current collector 10, and the composite current collector 10 includes a base film 101 and a first conductive layer 103 disposed on one surface of the base film 101, the positive electrode sheet 2 is in direct contact with the negative electrode sheet 1, the negative electrode material layer 11 of the negative electrode sheet 1 is adjacent to the base film 101 of the composite current collector of the positive electrode sheet 2, and the positive electrode material layer 21 of the positive electrode sheet 2 is adjacent to the base film 101 of the composite current collector of another negative electrode sheet 1. In the present application, the composite current collectors may be the same or different; the conductive layers in the composite current collectors may be the same or different. In some embodiments of the present application, when the thickness d1 of the base film satisfies 2≤d1≤10, no separator may be provided between the positive electrode sheet and the negative electrode sheet. It is understood that a separator may also be provided between the positive electrode sheet and the negative electrode sheet to prevent short circuit.

[0072] In some embodiments of the present application, the secondary battery includes two bipolar pole pieces and a separator arranged in a stacked manner, the bipolar pole piece includes a composite current collector, the composite current collector includes a base film and a conductive layer arranged on both surfaces of the base film, a positive electrode material layer is arranged on the surface of one conductive layer away from the base film, and a negative electrode material layer is arranged on the surface of the other conductive layer away from the base film. Figure 2 As shown, the secondary battery includes a bipolar pole piece 3 and a separator 4 which are stacked, the bipolar pole piece 3 includes a composite current collector 10, the composite current collector 10 includes a base film 101, a second conductive layer 102 and a first conductive layer 103, a negative electrode material layer 11 is arranged on the surface of the second conductive layer 102 away from the base film 101, a positive electrode material layer 21 is arranged on the surface of the first conductive layer 103 away from the base film 101, and a separator 4 is arranged between the two bipolar pole pieces 3, and the negative electrode material layer 11 of one bipolar pole piece 3 is arranged opposite to the positive electrode material layer 21 of the other bipolar pole piece 3. In the present application, the composite current collectors may be the same or different; the first conductive layer and the second conductive layer in the composite current collector may be the same or different.

[0073] In some embodiments of the present application, Figure 3As shown, the secondary battery includes a bipolar pole piece 3 and a composite current collector 10 which are stacked, the bipolar pole piece 3 includes the composite current collector 10, the composite current collector 10 includes a base film 101, a second conductive layer 102 and a first conductive layer 103, a negative electrode material layer 11 is arranged on the surface of the second conductive layer 102 away from the base film 101, and a positive electrode material layer 21 is arranged on the surface of the first conductive layer 103 away from the base film 101. A composite current collector 10 is arranged between two bipolar pole pieces 3, wherein the negative electrode material layer 11 of one bipolar pole piece 3 is arranged opposite to the second conductive layer 102 of the composite current collector 10 in the middle, and the positive electrode material layer 21 of the other bipolar pole piece 3 is arranged opposite to the first conductive layer 103 of the composite current collector 10 in the middle. It can be understood that in the present application, the second conductive layer 102 of the composite current collector 10 and the second conductive layer 102 of the composite current collector 10 in the bipolar pole piece 3 can be the same material, and the first conductive layer 103 of the composite current collector 10 and the first conductive layer 103 of the composite current collector 10 in the bipolar pole piece 3 can be the same material; the composite current collectors in the bipolar pole piece can be the same or different; the first conductive layer and the second conductive layer of the composite current collector in the bipolar pole piece can be the same or different.

[0074] In some embodiments of the present application, the composite current collector serves as an isolation membrane, allowing bidirectional transmission of lithium ions, which not only shortens the transmission path of lithium ions, but also helps shorten the transmission path of electrons, further improving the rate performance of the secondary battery.

[0075] In the present application, the negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.

[0076] In some embodiments of the present application, the negative electrode material layer may also include a negative electrode conductor, a negative electrode binder and a negative electrode thickener. The present application has no particular restrictions on the types of negative electrode conductors, negative electrode binders and negative electrode thickeners, as long as the purpose of the present application can be achieved. For example, the negative electrode conductor includes but is not limited to at least one of conductive carbon black, lamellar graphite, graphene, carbon nanotubes, carbon fibers, flake graphite, graphene, metal materials or conductive polymers. Conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The negative electrode binder may include, but is not limited to, at least one of polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium hydroxymethyl cellulose, or potassium hydroxymethyl cellulose. The negative electrode thickener may include, but is not limited to, at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, the negative electrode conductor, the negative electrode binder, and the negative electrode thickener in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0077] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 25 μm to 180 μm.

[0078] The positive electrode material layer of the present application includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to at least one of lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.

[0079] The positive electrode material layer may also include a positive electrode conductor and a positive electrode binder. The present application has no particular restrictions on the types of the positive electrode conductor and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may be at least one of the above-mentioned negative electrode conductors. The positive electrode binder may be at least one of the above-mentioned negative electrode binders. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0080] The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided positive electrode material layer is 30 μm to 300 μm.

[0081] In the present application, the isolation membrane is used to separate the bipolar pole pieces, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0082] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0083] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0084] In some embodiments of the present application, the inorganic layer includes inorganic particles and inorganic binders. The present application has no particular restrictions on inorganic particles, such as inorganic particles can include aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on inorganic binders, such as inorganic binders can be at least one of the above-mentioned negative electrode binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).

[0085] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 4 μm to 15 μm.

[0086] The secondary battery of the present application further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.

[0087] In some embodiments of the present application, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium hexafluorosilicate (LiSiF6), lithium bis(oxalatoborate) (LiBOB) and lithium difluoroborate (LiF2OB). The present application has no particular restrictions on the mass percentage of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. Based on the mass of the electrolyte, the mass percentage of the lithium salt can be 8% to 20%. For example, it may be 8%, 9%, 10%, 11%, 12%, 3%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range consisting of any two of these values.

[0088] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0089] The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0090] Examples of the above-mentioned linear carbonate compounds are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (EMC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) and combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate and combinations thereof.

[0091] Examples of the above carboxylic acid ester compounds are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerolactone, mevalonolactone, caprolactone and combinations thereof.

[0092] Examples of the above ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.

[0093] Examples of the above other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, phosphoric acid esters and combinations thereof.

[0094] The secondary battery also includes a shell for accommodating a positive electrode sheet, a negative electrode sheet and an electrolyte, or for accommodating a bipolar electrode sheet, a separator and an electrolyte, or for accommodating a bipolar electrode sheet, a composite current collector and an electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal, and a metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0095] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0096] The preparation process of the secondary battery is well known to those skilled in the art and is not particularly limited in the present application. For example, it may include but is not limited to the following steps: stacking the negative electrode sheet, the positive electrode sheet, the negative electrode sheet, and the positive electrode sheet in sequence, with a structure such as Figure 1 As shown, the electrode assembly of the winding structure is obtained by winding, folding, etc. as needed, the electrode assembly is placed in a shell, the electrolyte is injected into the shell and sealed to obtain a secondary battery; or, the four corners of the entire laminated structure are fixed with tape to obtain an electrode assembly of the laminated structure, the electrode assembly is placed in a shell, the electrolyte is injected into the shell and sealed to obtain a secondary battery.

[0097] For example, the steps may include but are not limited to: stacking the bipolar pole piece, the isolation film, and the bipolar pole piece in sequence, the structure being as follows: Figure 2 As shown, the electrode assembly of the winding structure is obtained by winding, folding, etc. as needed, the electrode assembly is placed in a shell, the electrolyte is injected into the shell and sealed to obtain a secondary battery; or, the four corners of the entire laminated structure are fixed with tape to obtain an electrode assembly of the laminated structure, the electrode assembly is placed in a shell, the electrolyte is injected into the shell and sealed to obtain a secondary battery.

[0098] For example, the following steps may be included but are not limited to: using a composite current collector having a first conductive layer and a second conductive layer as an isolation membrane, stacking a bipolar pole piece, an isolation membrane, and a bipolar pole piece in sequence, and the structure may be as follows: Figure 3 As shown, the electrode assembly of the winding structure is obtained by winding, folding, etc. as needed, the electrode assembly is placed in a shell, the electrolyte is injected into the shell and sealed to obtain a secondary battery; or, the four corners of the entire laminated structure are fixed with tape to obtain an electrode assembly of the laminated structure, the electrode assembly is placed in a shell, the electrolyte is injected into the shell and sealed to obtain a secondary battery.

[0099] Furthermore, an overcurrent prevention element, a guide plate, etc. may be placed in the housing as required to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0100] A third aspect of the present application provides an electronic device, which includes the secondary battery described in the second aspect of the present application.

[0101] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery or a lithium-ion capacitor, etc.

[0102] Example

[0103] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0104] Test methods and equipment:

[0105] Composite current collector sampling method:

[0106] The lithium-ion battery was discharged at a constant current of 0.5C to 3V, the lithium-ion battery was disassembled, and the composite current collector with a positive electrode material layer and / or a negative electrode material layer on the surface was taken out, and the positive electrode material layer and / or the negative electrode material layer on the surface was immersed in an N-methylpyrrolidone (NMP) solution at room temperature for 30 minutes, and then the positive electrode material layer and / or the negative electrode material layer was wiped with dust-free paper to remove the positive electrode material layer and / or the negative electrode material layer on the surface, and then ultrasonically cleaned in the NMP solution for 30 minutes at an ultrasonic frequency of 80 Hz to obtain a composite current collector.

[0107] Thickness test:

[0108] The composite current collectors of the embodiments and comparative examples were plasma cut longitudinally along the thickness direction to obtain a flat cross section, and the cross section was characterized using a Philips XL-30 field emission scanning electron microscope (SEM) with a magnification of 2000 times. The thickness of the base film and the conductive layer were observed and measured under the electron microscope.

[0109] The composite current collectors of the embodiments and comparative examples were plasma cut longitudinally along the thickness direction to obtain a flat cross section, and the cross section was characterized using a Philips XL-30 field emission scanning electron microscope (SEM) with a magnification of 2000 times. The thickness of the base film, the first metal layer or the first conductive carbon layer, and the second metal layer or the second conductive carbon layer were observed and measured under the electron microscope.

[0110] Composite current collector base film and conductive layer pore size test:

[0111] The composite current collectors of the embodiment and the comparative example were characterized by SEM (model: Philips XL-30) at a magnification of 10000 times. By observing the microstructure of the surface of the conductive layer, 3 images were randomly selected in a field of view of 10 μm×10 μm, and the pore sizes of all the conductive layers in the 3 images were measured, and the average value was taken as the pore size of the conductive layer;

[0112] The composite current collector was plasma cleaned to remove the conductive layer on the surface, and the pore size on the surface of the base membrane was characterized by SEM. The magnification of the SEM (model: Philips XL-30) characterization was 10,000 times. By observing the microstructure of the surface of the base membrane, 3 images were randomly selected in a field of view of 10μm×10μm, and the pore sizes of all base membranes in the 3 images were measured. The average value was taken as the pore size of the base membrane.

[0113] The above-mentioned apertures are all diameters of the circumscribed circles of the respective holes.

[0114] Porosity test of composite current collector base film and conductive layer:

[0115] Porosity = (apparent volume of sample - true volume of sample) / apparent volume of sample;

[0116] Apparent volume of the sample: Use a solid mold (5 cm × 10 cm) with an area of ​​S1 to punch out and measure the thickness h of the sample to obtain the apparent volume V of the sample. S =S1×h;

[0117] True volume of the sample: The test principle is to apply the Archimedean principle of gas displacement through the gas displacement method, and use the Bohr law (PV=nRT) of inert gas with small molecular diameter under certain conditions to measure the true volume of the sample being tested. Take the punched sample above, place it in the true density tester (model AccuPyc II 1345), close the test system, and introduce helium according to the procedure. By detecting the gas pressure in the sample chamber and the expansion chamber, the true volume is calculated according to Bohr's law:

[0118] (1)P1×(V cell -V samp )=n c RT a ;

[0119] (2)P a ×V exp =n e RT a :

[0120] When the valve is opened, the pressure drops to the intermediate value P2, and the mass conservation law becomes:

[0121] (3)P2×(V cell -V samp +V exp )=n c RT a +n e RT a ;

[0122] Then the true volume of the sample is: (4)V samp =(V cell -V exp )×(P2-P a ) / (P1-P2);

[0123] Among them, n c is the molar mass of the gas in the sample cup; n e is the molar mass of the gas in the expanding gas; R is the ideal gas constant; T a is the ambient temperature; V cell is the volume of the sample cup, V samp is the true volume of the sample; V exp is the volume of the expansion chamber; P1 is the gas pressure in the sample cup; P a is the gas pressure in the expansion chamber.

[0124] The volume V0 and porosity P0 of the composite current collector are measured in the above manner; the conductive layer is then removed by plasma cleaning to obtain a base film, and the volume V1 and porosity P1 of the base film are measured;

[0125] When the composite current collector includes a base film and a conductive layer disposed on one surface of the base film, the porosity of the conductive layer P2 (%) = (P0 × V0 - P1 × V1) / (V0 - V1);

[0126] When the composite current collector includes a base film, a first conductive layer and a second conductive layer, the base film is arranged between the first conductive layer and the second conductive layer, and the volume V0 and the porosity P0 of the composite current collector are measured in the above manner; then the second conductive layer is removed by plasma cleaning to obtain the base film and the first conductive layer, and the volume V11 and the porosity P11 of the base film and the first conductive layer are measured; then the porosity of the second conductive layer (%) = (P0×V0-P11×V11) / (V0-V11); then the first conductive layer is removed by plasma cleaning to obtain the base film, and the volume V1 and the porosity P1 of the base film are measured; then the porosity of the first conductive layer (%) = (P11×V11-P1×V1) / (V11-V1).

[0127] Composite current collector Young's modulus test:

[0128] Young's modulus refers to the ratio of tensile stress per unit area to the corresponding unit strain. A material testing machine (model: Shimadzu AGX-V2) can be used to take a composite current collector with a length of 5 cm and a tensile speed of 2 mm / min for a tensile test to obtain a curve of tensile stress and strain. The slope of the straight line part of the curve is calculated to obtain the Young's modulus of the composite current collector.

[0129] Conductive layer surface resistance test:

[0130] The four-probe test method is used, and the specific steps are as follows:

[0131] Arrange the needles of the four probes in a straight line at equal distances and record them as probes 1, 2, 3, and 4 respectively. Figure 4 As shown, the curvature radius of the probe tip is 25 μm, and the probe spacing is fixed at 1 mm; a pressure of 150 g is applied between the probe and the conductive layer, and the voltage V and current value I are obtained by the voltmeter and ammeter, and the surface square resistance R = (π / ln2)×(V / I) is calculated, where π is the pi.

[0132] Adhesion test between base film and conductive layer

[0133] Use the 180° peel test method for pressure-sensitive adhesive tape. The specific steps are as follows:

[0134] (1) Fix the composite current collector on the steel plate using double-sided tape. The size of the composite current collector is 70 mm in length and 20 mm in width.

[0135] (2) Paste 3M tape on the conductive layer surface of the composite current collector. The tape size is 15 mm in width and 50 mm in length.

[0136] (3) Use a tensile tester (model: Shimadzu AGX-V2) to peel off the 3M tape 180° at a speed of 10 mm / min to obtain the bonding force between the base film and the conductive layer in N / m.

[0137] Rate performance test:

[0138] The kinetic improvement effect on lithium-ion batteries is characterized by testing the capacity retention rate at different rates.

[0139] The voltage range is based on the voltage range marked on the outer packaging of the battery. For example, when the voltage range marked on the battery is 3.0V to 4.5V, the charging cut-off voltage is 4.5V and the discharging cut-off voltage is 3.0V. At 25°C, the lithium-ion battery is charged to 4.5V at a constant current of 1C, and then charged at a constant voltage at 4.5V to a current of 0.05C, allowed to stand for 5 minutes, and discharged at a constant current of 0.2C to a voltage of 3.0V. The discharge capacity of the lithium-ion battery at this time is recorded as C0; the lithium-ion battery is then charged to 4.5V at a constant current of 1C, and then charged at a constant voltage at 4.5V to a current of 0.05C, allowed to stand for 5 minutes, and discharged at a constant current of 0.5C to a voltage of 3.0V. The discharge capacity of the lithium-ion battery at this time is recorded as C1; the lithium-ion battery is then charged to 4.5V at a constant current of 1C, and then charged at a constant voltage at 4.5V to a current of 0.05C, allowed to stand for 5 minutes, and discharged at a constant current of 1C to a voltage of 3.0V. The discharge capacity of the lithium-ion battery at this time is recorded as C2; the lithium-ion battery is then charged to 4.5V at a constant current of 1C, and then charged at a constant voltage at 4.5V to a current of 0 .05C, let it stand for 5min, discharge at a constant current of 2C to a voltage of 3.0V, and record the discharge capacity of the lithium-ion battery at this time as C3; then charge the lithium-ion battery to 4.5V at a constant current of 1C, and then charge it at a constant voltage at 4.5V to a current of 0.05C, let it stand for 5min, and discharge it at a constant current of 3C to a voltage of 3.0V, and record the discharge capacity of the lithium-ion battery at this time as C4; then charge the lithium-ion battery to 4.5V at a constant current of 1C, and then charge it at a constant voltage at 4.5V to a current of 0.05C, let it stand for 5min, and discharge it at a constant current of 4C to a voltage of 3.0V, and record the discharge capacity of the lithium-ion battery at this time as C5; then charge the lithium-ion battery to 4.5V at a constant current of 1C, and then charge it at a constant voltage at 4.5V to a current of 0.05C, let it stand for 5min, and discharge it at a constant current of 6C to a voltage of 3.0V, and record the discharge capacity of the lithium-ion battery at this time as C6;

[0140] 0.5C discharge capacity retention rate (%) = C1 / C0 × 100%;

[0141] 1C discharge capacity retention rate (%) = C2 / C0×100%;

[0142] 2C discharge capacity retention rate (%) = C3 / C0×100%;

[0143] 3C discharge capacity retention rate (%) = C4 / C0×100%;

[0144] 4C discharge capacity retention rate (%) = C5 / C0×100%;

[0145] 6C discharge capacity retention rate (%) = C6 / C0×100%.

[0146] Lithium deposition performance:

[0147] The voltage range is based on the voltage range marked on the outer packaging of the battery. For example, when the voltage range marked on the battery is 3.0V to 4.5V, the charging cut-off voltage is 4.5V and the discharging cut-off voltage is 3.0V.

[0148] At room temperature, the lithium-ion battery is charged to 4.5V with a 3C constant current. At this time, the lithium-ion battery is in a fully charged state of 3C charging. Then the fully charged lithium-ion battery is disassembled to observe whether there is lithium deposition on the negative electrode. If gray-white granular matter is visually seen, it is lithium deposition.

[0149] The lithium-ion battery is charged to 4.5V at a constant current of 4C. At this time, the lithium-ion battery is in a fully charged state of 4C charging. Then the fully charged lithium-ion battery is disassembled to observe whether there is lithium deposition on the negative electrode plate.

[0150] The lithium-ion battery is charged at 6C constant current to 4.5V. At this time, the lithium-ion battery is in a fully charged state of 6C charging. Then the lithium-ion battery in the fully charged state is disassembled to observe whether there is lithium deposition on the negative electrode.

[0151] Observe whether there is lithium deposition on the negative electrode plate: if the area of ​​lithium deposition is less than 5% of the total area of ​​the negative electrode material layer of the negative electrode plate, it is slight lithium deposition; if the area of ​​lithium deposition is between 5% and 30% of the total area of ​​the negative electrode material layer of the negative electrode plate, it is lithium deposition; if the area of ​​lithium deposition is greater than 30% of the total area of ​​the negative electrode material layer of the negative electrode plate, it is severe lithium deposition.

[0152] Cycle performance test:

[0153] The voltage range is based on the voltage range marked on the outer packaging of the battery. For example, when the voltage range marked on the battery is 3.0V to 4.5V, the charging cut-off voltage is 4.5V and the discharging cut-off voltage is 3.0V.

[0154] At 25°C, the lithium-ion battery was charged and discharged for the first time. It was charged at a constant current of 0.2C to a cut-off voltage of 4.5V, and then charged at a constant voltage of 4.5V until the current was 0.05C. After standing for 5 minutes, it was discharged at a constant current of 0.2C to a cut-off voltage of 3.0V. The discharge capacity of the lithium-ion battery was measured to be A. Then, 500 cycles of charge and discharge were performed according to the above steps in an environment of 25°C. The discharge capacity of the lithium-ion battery at the 500th cycle was measured to be B, and the cycle capacity retention rate was calculated according to the following formula.

[0155] 500-cycle capacity retention rate (%) = B / A × 100%.

[0156] The larger the value of the cycle capacity retention rate obtained from the test, the better the cycle performance of the lithium-ion battery.

[0157] Example 1-1

[0158] <Preparation of Composite Current Collector>

[0159] Place the base film PI film on the sample stage of the thermal evaporator and evacuate it to a vacuum degree of ≤10 -6 Torr, set the sputtering instrument time to 10 min, and the sputtering rate to The sputtering temperature is 100°C, and the electron gun starts the electron beam to bombard the Al target until Al evaporates and vaporizes. The gaseous particles of Al are quickly transported to the surface of the PI film on the sample stage under vacuum, and nucleate and grow on a surface of the PI film to form a composite current collector A.

[0160] Composite current collector A includes a base membrane and a conductive layer arranged on one surface of the base membrane, the base membrane is a porous polyimide (PI) membrane, the porosity P1 of the base membrane is 60%, the pore size Φ1 is 600nm, and the thickness d1 is 5μm; the conductive layer includes a metal layer, the material of the metal layer includes aluminum, the porosity P2 of the conductive layer is 50%, the pore size Φ2 is 460nm, the thickness d2 is 1μm, and the surface resistance R is 30mΩ / sq; the bonding force between the base membrane and the conductive layer is 3N / m; and the Young's modulus E is 0.5GPa.

[0161] Place the base film PI film on the sample stage of the thermal evaporator and evacuate it to a vacuum degree of ≤10 -6 Torr, set the sputtering instrument time to 10 min, and the sputtering rate to The sputtering temperature is 100°C, and the electron gun starts the electron beam to bombard the Cu target until Cu evaporates and vaporizes. The gaseous particles of Cu are quickly transported to the surface of the PI film on the sample stage under vacuum, and nucleate and grow on a surface of the PI film to form a composite current collector B.

[0162] The composite current collector B includes a base film and a conductive layer arranged on one surface of the base film, the base film is a porous polyimide (PI) film, the porosity P1 of the base film is 60%, the pore size Φ1 is 600nm, and the thickness d1 is 5μm; the conductive layer includes a metal layer, the material of the metal layer includes copper, the porosity P2 of the conductive layer is 50%, the pore size Φ2 is 460nm, the thickness d2 is 1μm, and the surface resistance R is 25mΩ / sq; the bonding force between the base film and the conductive layer is 3N / m; the Young's modulus E of the composite current collector is 0.5GPa.

[0163] <Preparation of positive electrode sheet>

[0164] The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, and NMP is added as a solvent. The mixture is stirred and mixed to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 70wt%; the positive electrode slurry is evenly coated on the surface of the conductive layer of the composite current collector A (the conductive layer is aluminum) away from the base film, and dried at 120°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Dry under vacuum conditions at 120°C for 1h, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 42mm×49.2mm is obtained. Among them, the surface density of the positive electrode material layer is 17.38mg / cm 2 The compaction density of the cold pressing process is 4.23g / cm 3 .

[0165] <Preparation of negative electrode sheet>

[0166] After mixing the negative electrode active material artificial graphite, the negative electrode thickener sodium carboxymethyl cellulose (CMC-Na), and the negative electrode binder styrene-butadiene rubber (SBR) in a weight ratio of 95:2:3, deionized water is added as a solvent, and the mixture is stirred to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 75wt%; the negative electrode slurry is evenly coated on the surface of the conductive layer of the composite current collector B (the conductive layer is copper) away from the base film, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Dry under vacuum conditions at 120°C for 1h, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 43mm×50.2mm is obtained. Among them, the surface density of the negative electrode material layer is 9.21mg / cm 2 The compaction density of the cold pressing process is 1.75g / cm 3 .

[0167] <Preparation of Electrolyte>

[0168] In an environment with a water content of less than 10ppm, ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) are mixed in a weight ratio of 20:30:20:28:2 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) is added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the remainder is the base solvent.

[0169] <Preparation of lithium-ion batteries>

[0170] Through the lamination process, the negative electrode sheet, the positive electrode sheet, the negative electrode sheet, and the positive electrode sheet are stacked in order, such as Figure 1Then, the four corners of the entire laminate structure are fixed with tape to obtain an electrode assembly of the laminate structure, and the electrode assembly is placed in a shell aluminum-plastic film, dried at 80°C for 12 hours to remove moisture, injected with the above electrolyte and vacuum packaged, and a lithium-ion battery is obtained through a process of standing, forming, degassing, and shaping.

[0171] Example 1-2 to Example 1-6

[0172] Except for adjusting the sputtering rate of the conductive layer so that the porosity P2 of the conductive layer is as shown in Table 1 and adjusting the porosity P1 of the base film according to Table 1, the rest is the same as Example 1-1.

[0173] Example 1-7 to Example 1-12

[0174] Except for adjusting the sputtering rate of the conductive layer so that the aperture Φ2 of the conductive layer is as shown in Table 1 and adjusting the aperture Φ1 of the base film according to Table 1, the rest is the same as Example 1-1.

[0175] Example 1-13 to Example 1-19

[0176] Except for adjusting the sputtering weight per unit area of ​​the conductive layer so that the thickness d2 of the conductive layer is as shown in Table 1 and adjusting the thickness d1 of the base film according to Table 1, the rest is the same as Example 1-1.

[0177] Example 1-20 to Example 1-21

[0178] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0179] Examples 1-22

[0180] Except for adjusting the thickness d2 of the conductive layer so that the surface square resistance of the conductive layer is as shown in Table 1, the rest is the same as Example 1-1.

[0181] Example 1-23 to Example 1-24

[0182] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0183] Example 2-1

[0184] Except that the composite current collector is prepared according to the following steps, and in <Preparation of Positive Electrode Sheet>, the positive electrode slurry is evenly coated on the surface of the conductive carbon layer of the composite current collector away from the base film, and in <Preparation of Negative Electrode Sheet>, the negative electrode slurry is evenly coated on the surface of the conductive carbon layer of the composite current collector away from the base film, the rest is the same as Example 1-1.

[0185] <Preparation of Composite Current Collector>

[0186] First, the conductive carbon acetylene black, the binder styrene butadiene rubber, and the NMP solvent are mixed in a mass ratio of 3:1:96 to form a conductive carbon layer slurry. Then, the base film PI film is spread flat on the sample table, and the conductive carbon layer slurry is scraped on one surface of the PI film by scraping with a scalpel. Then, the base film coated with the conductive carbon layer slurry is placed in an oven and dried at 85°C for 1 hour. After the NMP evaporates, a composite current collector with a single-sided conductive carbon layer coating is obtained.

[0187] The composite current collector includes a base film and a conductive carbon layer arranged on one surface of the base film. The base film is a porous polyimide (PI) film, and the porosity P1 of the base film is 60%, the pore size Φ1 is 600nm, and the thickness d1 is 5μm. The material of the conductive carbon layer includes conductive carbon and a binder, the conductive carbon includes acetylene black, and the binder includes styrene-butadiene rubber. Based on the mass of the conductive carbon layer, the mass percentage W1 of the conductive carbon is 75%, and the mass percentage of the binder is 25%; the porosity P2 of the conductive carbon layer is 50%, the pore size Φ2 is 460nm, the thickness d2 is 1μm, and the surface square resistance R is 30mΩ / sq; the bonding force between the base film and the conductive layer is 70N / m; the Young's modulus E of the composite current collector is 0.5GPa.

[0188] Example 2-2 to Example 2-6

[0189] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 2-1.

[0190] Example 3-1

[0191] Except for preparing the composite current collector, the isolation membrane and the lithium-ion battery according to the following steps, the rest is the same as Example 2-1.

[0192] <Preparation of Composite Current Collector>

[0193] First, the first conductive carbon acetylene black, the first binder styrene butadiene rubber and the NMP solvent are mixed in a mass ratio of 3:1:96 to form a first conductive carbon layer slurry, and then the base film PI film is spread on the sample table, and the first conductive carbon layer slurry is spread on one surface of the PI film by scraping with a scalpel, and then the base film coated with the first conductive carbon layer slurry is placed in an oven at 85°C for 1h to dry, and the NMP is volatilized to obtain a composite current collector coated with the first conductive carbon layer, and then the composite current collector coated with the first conductive carbon layer is spread on the sample table with the other side facing up;

[0194] Then, the second conductive carbon acetylene black, the second binder styrene butadiene rubber and the NMP solvent are mixed in a mass ratio of 2:2:96 to form a second conductive carbon layer slurry, and the second conductive carbon layer slurry is scraped on the other surface of the PI film by a scalpel scraping method, and then placed in an oven and dried at 85°C for 1 hour. After the NMP is volatilized, a composite current collector coated with the first conductive carbon layer and the second conductive carbon layer is obtained.

[0195] The composite current collector includes a base film, a first conductive layer and a second conductive layer. The base film is arranged between the first conductive layer and the second conductive layer. The base film is a porous PI film with a porosity P1 of 60%, a pore size Φ1 of 600nm and a thickness d1 of 5μm.

[0196] The first conductive layer includes a first conductive carbon layer, the first conductive carbon layer includes a first conductive carbon and a first binder, the first conductive carbon includes acetylene black, and the first binder includes styrene-butadiene rubber; based on the mass of the first conductive carbon layer, the mass percentage W2 of the first conductive carbon is 75%, and the mass percentage of the first binder is 25%; the porosity P23 of the first conductive carbon layer is 50%, the pore diameter Φ23 is 460nm, the thickness d23 is 1μm, and the surface resistance R is 30mΩ / sq; the bonding force between the base film and the first conductive layer is 70N / m.

[0197] The second conductive layer includes a second conductive carbon layer, the second conductive carbon layer includes a second conductive carbon and a second binder, the second conductive carbon includes acetylene black, and the second binder includes styrene-butadiene rubber; based on the mass of the second conductive carbon layer, the mass percentage W3 of the second conductive carbon is 50%, and the mass percentage of the second binder is 50%; the porosity P24 of the second conductive layer is 50%, the pore diameter Φ24 is 460nm, the thickness d24 is 1μm, and the surface resistance R is 50mΩ / sq; the bonding force between the base film and the second conductive layer is 100N / m; the Young's modulus E of the composite current collector is 0.6GPa.

[0198] <Preparation of Separator Film>

[0199] The polyacrylate (solid content of 5 wt%) was stirred to form a uniform slurry, and the slurry was coated on both sides of the porous polyethylene substrate with a coating surface density of 0.9 mg / cm 2 After drying, an isolation film is formed, and the thickness of the isolation film is 6μm.

[0200] <Preparation of lithium-ion batteries>

[0201] The positive electrode slurry and the negative electrode slurry were prepared according to the steps in Example 1-1. The positive electrode slurry was coated on the surface of the first conductive layer of the composite current collector away from the base film, dried at 120°C and cold pressed, and the compacted density was 4.23 g / cm 3 ; The negative electrode slurry is coated on the surface of the second conductive layer of the composite current collector away from the base film, dried at 120°C and cold pressed, and the compaction density is 1.75g / cm 3 After being cut and stripped, bipolar pole pieces are formed, with specifications of 42mm×49.2mm. Among them, the surface density of the positive electrode material layer is 17.38mg / cm 2 The surface density of the negative electrode material layer is 9.21 mg / cm 2.

[0202] Through the lamination process, the bipolar pole piece, the isolation film, and the bipolar pole piece are stacked in sequence, such as Figure 2 Then, the four corners of the entire laminate structure are fixed with tape to obtain an electrode assembly of the laminate structure, and the electrode assembly is placed in a shell aluminum-plastic film, dried at 80°C for 12 hours to remove moisture, injected with the above electrolyte and vacuum packaged, and a lithium-ion battery is obtained through a process of standing, forming, degassing, and shaping.

[0203] Example 3-2 to Example 3-7

[0204] Except for adjusting the relevant preparation parameters according to Table 5, the rest is the same as Example 3-1.

[0205] Embodiment 3-8

[0206] Except for preparing the isolation membrane and lithium-ion battery according to the following steps, the rest is the same as Example 3-1.

[0207] <Preparation of Separator Film>

[0208] The composite current collector in Example 3-1 was selected as the isolation membrane.

[0209] <Preparation of lithium-ion batteries>

[0210] The positive electrode slurry and the negative electrode slurry were prepared according to the steps in Example 1-1. The positive electrode slurry was coated on the surface of the first conductive layer of the composite current collector away from the base film, dried at 120°C and cold pressed, and the compacted density was 4.23 g / cm 3 The negative electrode slurry is coated on the surface of the second conductive layer of the composite current collector away from the base film, dried at 120°C and cold pressed, and the compaction density is 1.75g / cm 3 After being cut and stripped, bipolar pole pieces are formed, with specifications of 42mm×49.2mm. Among them, the surface density of the positive electrode material layer is 17.38mg / cm 2 The surface density of the negative electrode material layer is 9.21 mg / cm 2 .

[0211] Through the lamination process, the bipolar pole piece, the isolation film, and the bipolar pole piece are stacked in sequence, such as Figure 3 Then, the four corners of the entire laminate structure are fixed with tape to obtain an electrode assembly of the laminate structure, and the electrode assembly is placed in a shell aluminum-plastic film, dried at 80°C for 12 hours to remove moisture, injected with the above electrolyte and vacuum packaged, and a lithium-ion battery is obtained through a process of standing, forming, degassing, and shaping.

[0212] Example 3-9 to Example 3-12

[0213] Except for adjusting the relevant preparation parameters according to Table 5, the rest is the same as Example 3-8.

[0214] Comparative Example 1

[0215] <Preparation of positive electrode sheet>

[0216] The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, and NMP is added as a solvent. The mixture is stirred and mixed evenly to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 70wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 120°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 120°C for 1h, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 42mm×49.2mm is obtained. Among them, the surface density of the positive electrode material layer is 17.38mg / cm 2 The compaction density of the cold pressing process is 4.23g / cm 3 .

[0217] <Preparation of negative electrode sheet>

[0218] After mixing the negative electrode active material artificial graphite, the negative electrode thickener sodium carboxymethyl cellulose (CMC-Na), and the negative electrode binder styrene-butadiene rubber (SBR) in a weight ratio of 95:2:3, deionized water is added as a solvent, and the mixture is stirred to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 75wt%; the negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Dry under vacuum conditions at 120°C for 1h, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 43mm×50.2mm is obtained. Among them, the surface density of the negative electrode material layer is 9.21mg / cm 2 The compaction density of the cold pressing process is 1.75g / cm 3 .

[0219] <Preparation of Separator Film>

[0220] The polyacrylate (solid content of 5 wt%) was stirred to form a uniform slurry, and the slurry was coated on both sides of the porous polyethylene substrate with a coating surface density of 0.9 mg / cm 2 After drying, an isolation film is formed, and the thickness of the isolation film is 6μm.

[0221] <Preparation of Electrolyte>

[0222] In an environment with a water content of less than 10ppm, ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) are mixed in a weight ratio of 20:30:20:28:2 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) is added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the remainder is the base solvent.

[0223] <Preparation of lithium-ion batteries>

[0224] Through the lamination process, the positive electrode sheet, the separator, and the negative electrode sheet are stacked in order. Then the four corners of the entire lamination structure are fixed with tape to obtain the electrode assembly of the lamination structure. The electrode assembly is placed in the shell aluminum plastic film, and after dehydration at 80°C, the above electrolyte is injected and vacuum packaged. After the static, formation, degassing, and shaping process, the lithium-ion battery is obtained.

[0225] Comparative Examples 2 to 7

[0226] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0227] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 6.

[0228] Table 1

[0229]

[0230]

[0231] Note: “ / ” in Table 1 indicates that there is no corresponding preparation parameter, substance or performance parameter.

[0232] Table 2

[0233]

[0234]

[0235] It can be seen from Examples 1-1 to 1-24 and Comparative Examples 1 to 7 that when the structure of the composite current collector, the porosity and pore size of the base film and the conductive layer are within the scope of the present application, the lithium ion battery prepared using the composite current collector provided by the present application has a higher 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium deposition performance, indicating that the rate performance of the lithium ion battery can be improved, and the lithium ion battery has better cycle performance and better lithium deposition performance. The types of the positive electrode current collector and the negative electrode current collector of Comparative Example 1 are not within the scope of the present application, the porosity and pore size of the base film and / or the conductive layer in the composite current collectors provided in Comparative Examples 2 to 7 are not within the scope of the present application, and the lithium ion battery has a low 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and poor lithium plating performance, indicating that the rate performance, cycle performance and lithium plating performance of the lithium ion battery are relatively poor.

[0236] from Figure 5 It can be seen that the pore size distribution of the composite current collector base film is uniform. Figure 6 It can be seen that the composite current collector conductive layer prepared in Example 1-1 of the present application includes a metal layer, and when the material of the metal layer includes copper, the pore size distribution of the conductive layer is uniform. Figure 7 It can be seen that when the composite current collector conductive layer prepared in Example 1-1 of the present application includes a metal layer, and the material of the metal layer includes aluminum, the pore size distribution of the conductive layer is relatively uniform.

[0237] The thickness of the base film and the conductive layer will affect the rate, cycle and lithium deposition performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-13 to 1-19 that the thickness of the base film and the conductive layer is within the scope of this application, and the prepared lithium-ion battery has a high 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium deposition performance, indicating that the rate performance of the lithium-ion battery can be improved, and the lithium-ion battery has good cycle performance and better lithium deposition performance.

[0238] The material of the base film will affect the rate, cycle and lithium deposition performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-20 and 1-21 that the material of the base film is within the scope of this application, and the prepared lithium-ion battery has a high 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium deposition performance, indicating that the rate performance of the lithium-ion battery can be improved, and the lithium-ion battery has good cycle performance and better lithium deposition performance. Compared with Example 1-1, Example 1-20 has a smaller bonding force between the base film and the conductive layer due to the different base film materials of Example 1-20, which will affect the conductivity, resulting in a larger surface square resistance of the conductive layer of Example 1-20; Compared with Example 1-1, Example 1-21 has a larger bonding force between the base film and the conductive layer due to the different base film materials of Example 1-21, which will help improve the conductivity, resulting in a smaller surface square resistance of the conductive layer of Example 1-21.

[0239] The material of the conductive layer will affect the rate, cycle and lithium deposition performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-23 and 1-24 that the material of the conductive layer is within the scope of this application, and the prepared lithium-ion battery has a high 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium deposition performance, indicating that the rate performance of the lithium-ion battery can be improved, and the lithium-ion battery has good cycle performance and better lithium deposition performance.

[0240] The values ​​of P1 / P2, Φ1 / Φ2, and d1 / d2 will affect the rate, cycle, and lithium deposition performance of the lithium-ion battery. From Example 1-1, Example 1-4 to Example 1-6, Example 1-11 to Example 1-12, and Example 1-16 to Example 1-19, it can be seen that the values ​​of P1 / P2, Φ1 / Φ2, and d1 / d2 are within the scope of this application, and the prepared lithium-ion battery has a higher 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate, and better lithium deposition performance, indicating that the rate performance of the lithium-ion battery can be improved, and the lithium-ion battery has better cycle performance and better lithium deposition performance. Compared with Example 1-1, Example 1-13 to Example 1-15, Example 1-18, and Example 1-19, Example 1-16 has thicker base film and conductive layer thicknesses, which will affect the energy density of the lithium-ion battery.

[0241] The surface square resistance of the conductive layer will affect the rate, cycle and lithium precipitation performance of the lithium ion battery. It can be seen from Examples 1-1 to 1-24 that the surface square resistance of the conductive layer is within the scope of this application, and the prepared lithium ion battery has a higher 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium precipitation performance, indicating that the rate performance of the lithium ion battery can be improved, and the lithium ion battery has better cycle performance and better lithium precipitation performance. It can be seen from Examples 1-1 and 1-22 that the rate performance, cycle performance and lithium precipitation performance of the lithium ion battery prepared in Examples 1-22 and 1-1 are close, but the thickness of the conductive layer of the composite current collector of Example 1-22 is larger, the surface square resistance of the conductive layer is smaller, and the energy density of the prepared lithium ion battery is lower.

[0242] Table 3

[0243]

[0244] Table 4

[0245]

[0246] The bonding force between the base film and the conductive layer will affect the rate, cycle and lithium deposition performance of the lithium ion battery. From Examples 1-1 to 1-24 and 2-1 to 2-6, it can be seen that the bonding force between the base film and the conductive layer is within the scope of the present application, and the prepared lithium ion battery has a high 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium deposition performance, indicating that the rate performance of the lithium ion battery can be improved, and the lithium ion battery has better cycle performance and better lithium deposition performance.

[0247] The material of the conductive carbon layer and the mass percentage of the conductive carbon will affect the rate, cycle and lithium precipitation performance of the lithium-ion battery. It can be seen from Examples 2-1 to 2-6 that the material of the conductive carbon layer and the mass percentage of the conductive carbon are within the scope of this application, and the prepared lithium-ion battery has a higher 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium precipitation performance, indicating that the rate performance of the lithium-ion battery can be improved, and the lithium-ion battery has better cycle performance and better lithium precipitation performance. It can be seen from Examples 2-3 and 2-1 that the conductive carbon content of Example 2-1 is higher, the electronic conductivity of the composite current collector is better, the rate performance and lithium precipitation performance of Example 2-1 are better, and the cycle performance is better.

[0248]

[0249] Table 6

[0250]

[0251] The material of the first conductive carbon layer, the mass percentage of the first conductive carbon, the material of the second conductive carbon layer, and the mass percentage of the second conductive carbon will affect the rate, cycle and lithium deposition performance of the lithium ion battery. From Example 3-1 to Example 3-5, it can be seen that the material of the first conductive carbon layer, the mass percentage of the first conductive carbon, the material of the second conductive carbon layer, and the mass percentage of the second conductive carbon are within the scope of this application, and the prepared lithium ion battery has a higher 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium deposition performance, indicating that the rate performance of the lithium ion battery can be improved, and the lithium ion battery has better cycle performance and better lithium deposition performance.

[0252] In Example 2-1, the composite current collector includes a base film and a conductive carbon layer disposed on one surface of the base film, and a negative electrode material layer or a positive electrode material layer is disposed on the surface of the conductive carbon layer; in Example 3-1, the composite current collector includes a base film and conductive carbon layers disposed on both surfaces of the base film, and a positive electrode material layer is disposed on the surface of one conductive carbon layer away from the base film, and a negative electrode material layer is disposed on the surface of the other conductive carbon layer away from the base film. It can be seen from Example 2-1 and Example 3-1 that the rate performance, cycle performance and lithium precipitation performance of the lithium-ion batteries prepared in Example 2-1 and Example 3-1 are similar, but in Example 3-1, conductive carbon layers are disposed on both surfaces of the base film of the composite current collector, and the thickness thereof is relatively large, and the energy density of the prepared lithium-ion battery is relatively low. The value of W2 / W3 will affect the rate, cycle and lithium precipitation performance of the lithium-ion battery. It can be seen from Example 3-1, Example 3-6 to Example 3-7 that the value of W2 / W3 is within the scope of the present application, and the prepared lithium ion battery has a higher 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium deposition performance, indicating that the rate performance of the lithium ion battery can be improved, and the lithium ion battery has good cycle performance and better lithium deposition performance.

[0253] It can be seen from Examples 3-8 to 3-12 that when the composite current collector is used as an isolation membrane, the prepared lithium-ion battery has higher 0.5C discharge capacity retention rate, 1C discharge capacity retention rate, 2C discharge capacity retention rate, 3C discharge capacity retention rate, 4C discharge capacity retention rate, 6C discharge capacity retention rate, 500 cycle capacity retention rate and better lithium plating performance, indicating that the rate performance of the lithium-ion battery can be improved, and the lithium-ion battery has better cycle performance and better lithium plating performance.

[0254] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0255] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0256] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A composite current collector, comprising a base film and a conductive layer arranged on at least one surface of the base film, the base film comprising at least one of a polypropylene film, a polyethylene film, a polyimide film or an aramid film, the porosity of the base film being P1%, 30≤P1≤80, the pore size of the base film being Φ1nm, 200≤Φ1≤1000, the porosity of the conductive layer being P2%, 10≤P2≤75, the pore size of the conductive layer being Φ2nm, 100≤Φ2≤800.

2. The composite current collector according to claim 1, wherein: 500≤Φ1≤800, and / or 300≤Φ2≤600.

3. The composite current collector according to claim 1, wherein: 1≤P1 / P2≤2, and / or 1≤Φ1 / Φ2≤2.

4. The composite current collector according to claim 1, wherein: The thickness of the base film is d1 μm, 2≤d1≤10.

5. The composite current collector according to claim 4, wherein: The thickness of the conductive layer is d2 μm, 0.1≤d2≤5.

6. The composite current collector according to claim 5, wherein: 5≤d1 / d2≤10.

7. The composite current collector according to claim 1, wherein: The surface resistance of the conductive layer is R mΩ / sq, 10≤R≤50.

8. The composite current collector according to any one of claims 1 to 7, wherein: The composite current collector includes the base film and the conductive layer disposed on one surface of the base film, wherein the conductive layer includes any one of a metal layer and a conductive carbon layer; The material of the metal layer includes any one of copper, aluminum, zinc, titanium, nickel or silver; The conductive carbon layer comprises conductive carbon and a binder, wherein the conductive carbon comprises at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the binder comprises at least one of polyvinylidene fluoride, styrene-butadiene rubber or acrylate; Based on the mass of the conductive carbon layer, the mass percentage of the conductive carbon is W1%, 50≤W1≤95.

9. The composite current collector according to claim 1, wherein: The composite current collector includes the base film, a first conductive layer and a second conductive layer, the base film is arranged between the first conductive layer and the second conductive layer, the first conductive layer includes a first metal layer, the second conductive layer includes a second metal layer, the material of the first metal layer includes at least one of aluminum, nickel or silver, and the material of the second metal layer includes at least one of copper, nickel or silver.

10. The composite current collector according to claim 1, wherein: The composite current collector comprises the base film, a first conductive layer and a second conductive layer, wherein the base film is disposed between the first conductive layer and the second conductive layer; The first conductive layer includes a first conductive carbon layer, the second conductive layer includes a second conductive carbon layer, the first conductive carbon layer includes a first conductive carbon and a first binder, the second conductive carbon layer includes a second conductive carbon and a second binder, the first conductive carbon and the second conductive carbon are each independently selected from at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the first binder and the second binder are each independently selected from at least one of polyvinylidene fluoride, styrene-butadiene rubber or acrylate; Based on the mass of the first conductive carbon layer, the mass percentage of the first conductive carbon is W2%, based on the mass of the second conductive carbon layer, the mass percentage of the second conductive carbon is W3%, and 1<W2 / W3≤2.

11. The composite current collector according to claim 1, wherein: The adhesive force between the base film and the conductive layer is 2 N / m to 200 N / m. 12 . A secondary battery comprising the composite current collector according to claim 1 . 13 . An electronic device comprising the secondary battery according to claim 12 .

Citation Information

Cited By

  • Composite separator, secondary battery, and electric device

    CN120033420A

  • Composite separator, secondary battery, and electrical device

    CN120033420B

  • Functional current collector and preparation method therefor, and electrochemical device

    WO2026194513A1